2015
DOI: 10.3389/fpls.2014.00795
|View full text |Cite
|
Sign up to set email alerts
|

Transcription profiles of boron-deficiency-responsive genes in citrus rootstock root by suppression subtractive hybridization and cDNA microarray

Abstract: Boron (B) deficiency has seriously negative effect on citrus production. Carrizo citrange (CC) has been reported as a B-deficiency tolerant rootstock. However, the molecular mechanism of its B-deficiency tolerance remained not well-explored. To understand the molecular basis of citrus rootstock to B-deficiency, suppression subtractive hybridization (SSH) and microarray approaches were combined to identify the potential important or novel genes responsive to B-deficiency. Firstly four SSH libraries were constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 70 publications
5
41
0
Order By: Relevance
“…It has been proven that plant roots are affected by B deficiency as a result of the role of B in cell wall construction (Dell and Huang, 1997;Marschner, 1995). Similar results have also been reported for the roots of other citrus (Li et al, 2016;Mei et al, 2016;Zhou et al, 2014Zhou et al, , 2015Wu et al, 2018). Further plant anatomical investigations of the roots of citrus (Li et al, 2016;Mei et al, 2016;Zhou et al, 2015) suffering from B starvation stress have been performed, and these results indicated that the root cell and vessel walls were thickened under B deficiency conditions.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It has been proven that plant roots are affected by B deficiency as a result of the role of B in cell wall construction (Dell and Huang, 1997;Marschner, 1995). Similar results have also been reported for the roots of other citrus (Li et al, 2016;Mei et al, 2016;Zhou et al, 2014Zhou et al, , 2015Wu et al, 2018). Further plant anatomical investigations of the roots of citrus (Li et al, 2016;Mei et al, 2016;Zhou et al, 2015) suffering from B starvation stress have been performed, and these results indicated that the root cell and vessel walls were thickened under B deficiency conditions.…”
Section: Discussionsupporting
confidence: 82%
“…1). Corky split vein is a typical symptom of citrus that have been proved in various citrus while suffering from B starvation stress (Han et al, 2008;Liu et al, 2011b;Yang et al, 2013Yang et al, , 2015Zhou et al, 2014Zhou et al, , 2015. Other symptoms were also observed under B deficiency at different pH values, with more severe symptoms observed at pH 4.0 and pH 5.0 than at pH 6.0 (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…In field, B availability can be affected by several factors, changing over time and the space. Given that gene transcriptional regulation occurs within few hours after the onset of stress (Zhou et al, 2015) and, as revealed by the hydroponic experiment, grapevine leaf tissues can be considered a good target for the study of plant response to B bioavailability, the transcript levels of the B transporters were measured in leaf collected immediately after GMLD symptom occurrence. While neither the GPGV variant nor the virus titer seemed to be linked to GLMD symptom expression, the differential regulation of VvBOR3, VvNIP5, and VvNIP6 genes between symptomatic and asymptomatic plants hints at the importance of changes in B homeostasis as a trigger for GLMD symptom expression.…”
Section: In the Field Glmd Symptom Expression May Be Associated Withmentioning
confidence: 99%
“…Fluorescent dyelabeled cDNA and hybridization were prepared according to a previous published protocol (Guo et al, 2005). Microarray data and EST sequence analysis had been carried out during our previously published study (Zhou et al, 2015).…”
Section: Microarray Analysismentioning
confidence: 99%